Pengawasan Pemeliharaan Sarana Prasarana di SMAN 1 Tulung Selapan - Rohimin, Muhammad; Annur, Saipul; Ibrahim, Ibrahim (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this research is to understand the process of supervising the maintenance of facilities and infrastructure at SMA Negeri 1 Tulung Selapan, Ogan Komering Ilir Regency, South Sumatra. This study employs a descriptive research type with a qualitative approach. The key informants in this research are the principal and the vice principal for facilities and infrastructure, while the supporting informants are the teachers. Data collection techniques used include interviews, observations, and documentation. Data analysis techniques involve data reduction, data presentation, and data verification or conclusion drawing. The results of this study show that the supervision of facilities and infrastructure maintenance has been carried out well and has led to many positive changes in the school, improving conditions through the implementation of maintenance supervision, which includes awareness, understanding, organization, implementation, and documentation. Supporting factors for the supervision of facilities and infrastructure maintenance include the availability of human resources and good communication. The inhibiting factor is the lack of available funds.